Transformation of financial markets under the influence of ESG principles - Kurbanova , К.А.; Nurmagambetova , A.Z.; Kurbanbayeva , A.A.; Beissenova , G.Sh.; Berdimurat, А. (BUKETOV BUSINESS REVIEW, 2024)
Object: This article explores how the introduction of ESG standards is changing financial markets and influencing investment decision-making in different countries. Methods Within the framework of this study, comprehensive analysis methods are used to assess the impact of the implementation of ESG principles on financial markets and investment decisions in various countries. The methodology includes both qualitative and quantitative approaches, which makes it possible to deeply explore both global and regional features. Results: As a result of the study, it is planned to assess the impact of ESG principles on financial markets, identify changes in investment flows, the development of new financial instruments and the market value of companies with different levels of ESG ratings. There will also be a comparison of approaches to the implementation of ESG in different countries and regions, which will identify key differences in regulatory and market practices. Special attention will be paid to analyzing how investors make decisions in the context of the growing importance of sustainable standards, as well as identifying risks and barriers faced by companies and financial markets. Based on the results obtained, recommendations will be proposed to further improve the integration of ESG principles into financial systems. Conclusions: ESG principles significantly influence the transformation of financial markets, changing investment strategies and the market value of companies. Differences in approaches to the implementation of ESG in different countries related to the peculiarities of regulation and levels of market development have been identified. ESG factors are becoming an important criterion for investors, but there are risks and barriers, such as problems with data standardization and sustainability assessment. It is recommended to strengthen the integration of ESG principles into financial systems to increase their sustainability and attractiveness to investors.